The Transatlantic Trade and Investment Partnership (TTIP): a controversial agreement and dangerous for workers - Serfati, Claude (Brussels, 2015)
"This Working Paper on the Transatlantic Trade and Investment Partnership (TTIP) highlights the controversial benefits of speeding up free trade and puts the negotiations between the EU and the US in the context of the fall-out of the financial crisis. It looks at the contentious issues of public procurement and harmonisation of standards, agriculture, the environment and the investor/state dispute. It explains why trade unions fear that TTIP will set the scene for social dumping and concludes by looking at opportunities for the labour movement to use the 'cracks in the common front of business and governments'."